Zinc Deficiency in Humans and its Amelioration - Shivay, Yashbir Singh (Indian Journal of Community Health, 2015)
Zinc (Zn) deficiency in humans has recently received considerable attention. Global mortality in children under 5 years of age in 2004 due to Zn deficiency was estimated at 4,53,207 as against 6,66,771 for vitamin A deficiency; 20,854 for iron deficiency and 3,619 for iodine deficiency. In humans 2800-3000 proteins contain Zn prosthetic group and Zn is an integral component of zinc finger prints that regulate DNA transcription. Zinc is a Type-2 nutrient, which means that its concentration in blood does not decrease in proportion of the Zn deficiency. Adverse effects of Zn deficiency vary with age: low weight gain, diarrhoea, aneroxia and neurobehavioral disturbances are observed in infants, while skin changes and dwarfism are frequent in toddlers and adolescents. Common manifestations of Zn deficiency among elderly include hypogeusia, chronic non-healing ulcers and recurrent infections. Ameliorative measures of Zn deficiency in humans can be classified in two groups, namely, nutraceutical and biofortification of food grains. Nutraceutical interventions include pharmaceutical supplements, dietary supplements and dietary diversification, while biofortification of food grains can be achieved by genetic modification (GM) of crops or by agronomic techniques that include soil or/and foliar fertilization of crops. The major disadvantage of nutraceutical approaches is that the major beneficiaries are urban people and the poor rural masses that need adequate Zn nutrition most are left out. Genetic biofortification of food grains requires large amounts of funds and a fairly long-period of time. Further, a large number of countries have not yet accepted genetically modified (GM) foods. On the other hand agronomic biofortification of food grains yields immediate effects and rural and urban people are equally benefitted. Our studies have shown that Zn concentration in cereals (rice, wheat etc) and pulses can be considerably increased by soil or/and foliar fertilization of cereal and pulse crops with Zn. Needless to add that cereals and pulses are the major components of a vegetarian human diet in India.